Hack proofing Linux a guide to open source security - Stanger, James (Rockland, Mass. : Syngress Media ; London : International Thomson, 2001)
From the authors of the bestselling E-Mail Virus Protection Handbook! The Linux operating system continues to gain market share based largely on its reputation as being the most secure operating system available. The challenge faced by system administrators installing Linux is that it is secure only if installed and configured properly, constantly and meticulously updated, and carefully integrated with a wide variety of Open Source security tools. The fact that Linux source code is readily available to every hacker means that system administrators must continually learn security and anti-hacker techniques. Hack Proofing Linux will provide system administrators with all of the techniques necessary to properly configure and maintain Linux systems and counter malicious attacks. * Linux operating systems and Open Source security tools are incredibly powerful, complex, and notoriously under-documented - this book addresses a real need * CD-Rom contains Red Hat/Mandrake Linux RPMs as well as tarballs for other Linux distributions and the BSD community * Uses forensics-based analysis to give the reader an insight to the mind of a hacker.
Includes index.
Keywords: Linux; Computer security; Electronic books